2021
DOI: 10.3389/fdmed.2021.687507
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Adverse Effects of Over-the-Counter Whitening Products on Dental Tissues

Abstract: The role of bleaching agents (e.g., hydrogen peroxide) in tooth bleaching is quite well-described in a few literature studies and considered as the option choice for those desiring brighter teeth, but alternative methods have emerged to fulfill the desire of patients in a faster, easier, and cheaper way. In this context, whitening over-the-counter (OTC) products are available in several vehicles, such as toothpaste, rinses, gums, paint-on varnishes, and strips, but their effectiveness in terms of bleaching is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 76 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…There are formulations specifically designed to have a whitening action, which includes chemicals such as peroxides, citrates, and pyrophosphates, as well as certain enzymes and surfactants. 21 , 22 The findings found in the studies showed that the toothpastes and mouthwashes with whitening action did not have a favorable effect on the outcomes evaluated and in some cases did not show differences with the control group or with regular toothpastes and mouthwashes.…”
Section: Discussionmentioning
confidence: 92%
“…There are formulations specifically designed to have a whitening action, which includes chemicals such as peroxides, citrates, and pyrophosphates, as well as certain enzymes and surfactants. 21 , 22 The findings found in the studies showed that the toothpastes and mouthwashes with whitening action did not have a favorable effect on the outcomes evaluated and in some cases did not show differences with the control group or with regular toothpastes and mouthwashes.…”
Section: Discussionmentioning
confidence: 92%
“…This might be attributed to the design of OTC-paint on gel products where there is no physical barrier to protect the active materials from oral environment and enhance the contact with the tooth surface [24]. In addition, the reduced CP concentration in these products decreases the whitening efficiency [25]. This may encourage patients to overuse these products to get the expected aesthetic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Once the stain etiology is identified, dentists shall propose an individualized treatment to each patient considering their wishes, expectations, dental condition, and oral health. 3 Usually, tooth bleaching is carried out in the office with more concentrated gels and reduced application time (in-office technique), or at home, under the dentist's supervision, with less concentrated gels and longer application time (athome technique). [4][5][6] Moreover, there is a niche in the oral care market comprising toothpastes, rinses, paint-on varnishes, gels, strips and flosses with bleaching or whitening properties, known as over-the-counter (OTC) products.…”
Section: Introductionmentioning
confidence: 99%